Serendipitous discovery of a dusty disc around WDJ181417.84−735459.83. Issue 3 (12th December 2020) - González Egea, E; Raddi, R; Koester, D; Rogers, L K; Marocco, F; Cooper, W J; Beamin, J C; Burningham, B; Day−Jones, A; Forbrich, J; Pinfield, D J
ABSTRACT: Spectroscopic observations of white dwarfs reveal that many of them are polluted by exoplanetary material, whose bulk composition can be uniquely probed this way. We present a spectroscopic and photometric analysis of the DA white dwarf WDJ181417.84−735459.83, an object originally identified to have a strong infrared (IR) excess in the 2MASS and WISE catalogues that we confirmed to be intrinsic to the white dwarf, and likely corresponding to the emission of a dusty disc around the star. The finding of Ca, Fe, and Mg absorption lines in two X-SHOOTER spectra of the white dwarf, taken 8 years apart, is further evidence of accretion from a dusty disc. We do not report variability in the absorption lines between these two spectra. Fitting a blackbody model to the IR excess gives a temperature of 910 ± 50 K. We have estimated a total accretion flux from the spectroscopic metal lines of $|\dot{\rm M}| = 1.784 × 10^{9}\, $ g s −1 .